O direito de resistência e o tiranicídio no pensamento político de Juan de Mariana : contextualização, apresentação e a justificação do direito de resistência - Silva, Lucas Duarte (2017)
The work’s research object is the problem of tyranny and the right of slay a tyrant in Juan de Mariana, S. J (1536-1624), famous Spanish theologian who became known in the History of Ideas as a defender of tyrannicide. We want to understand how the Jesuit presents and justifies the Right of Resistance in his works De rege et regis institutione and De monetae mutatione. Our hypothesis will be the Right of Resistance is treated by Mariana as a natural and inalienable right of men. Due to its nature, any man, private or public authority, has the right to depose an illegitimate ruler who threatens the citizens life and wellbeing. This defence of private citizen action against the tyrant is pointed out as an "innovation" of Juan de Mariana in ahead of the thinkers of his time. Therefore, other objective of this work is to determine the backgrounds of his position and what extent the Jesuit would have contributed “originally” to the problem of tyranny. We will try to defend Mariana as a followed of "Thomist tradition" in the treatment of this subject. To this end, we will divide the following text into three chapters. In the first, we shall try to trace how the tyrant's problem and the Right of Resistance developed from the Middle Ages to Juan de Mariana. In order to keep this chapter shorter, we shall keep ourselves to the reflections of Salisbury, Thomas Aquinas, Francisco de Vitoria, and Domingo de Soto. We will also deal, in this chapter, with the French and Spanish political context of the sixteenth century. We believe that will be important for the development of this work for two main reasons: first to understand what would be "a Thomistic tradition justification of the Right of Resistance"; second, because we judge important to understand our research object inserted in its context and the various forms that this right was evoked. In the second chapter, we will try to deal with the main political elements and concepts of Jesuit thought, namely: the origin of the state; the main forms of government; the definition of law and the role of natural law; the relationship between the ruler, the laws and state institutions. Thus, with this general approach of Mariana’s thought, we must be able to show how the Right of Resistance, and the right to slay a tyrant, is consistent with them. Finally, in the third chapter, we will explain in detail how Mariana understood and justified the Right of Resistance in the natural principle of self-defense. We will also settle on other important aspects, such as the characterization of the king and the tyrant, the maxims of real action, in particular, the virtues of prudence and justice, the circumstances and manner of execution the Right of Resistance, among other elements.